Binding of Procaine Hydrochloride to Hydrocarbon and Fluorocarbon Surfactants: The Role of Hydrophobicity - (:unkn) unknown (SCIENCEDOMAIN INT, 2018)
Aims: The interaction of procaine hydrochloride (PC HCl) with sodium dodecyl sulfate (anionic hydrocarbon surfactant; SDS), Tween 20 (nonionic hydrocarbon surfactant), cetyltrimethyl ammonium bromide (cationic hydrocarbon surfactant; CTAB), lauryl sulphate betaine (amphoteric hydrocarbon surfactant; LSB) and Zonyl-FSN100 (non-ionic fluorocarbon surfactant; Zonyl FSN) has been aimed to study by UV-vis spectrophotometry. Methodology: Interactions with a fixed concentration of PC HCl in the wide concentration range of Tween 20, Zonyl FSN, SDS, CTAB and LSB were studied spectrophotometrically at 298 K. Binding constants of PC HCl to micelles was determined by using the Benesi-Hildebrand Equation. Results: Comparison of the binding constants (K-B) showed that the most binding tendency of PC HCl to micelles in case of Zonyl FSN. Due to the electrostatic repulsion between cationic CTAB and cationic PC HCl the binding constant could not be calculated. The effect of Zonyl FSN on the binding of PC HCl to hydrocarbon micelles has been also studied in the presence of fixed micelle concentration of Zonyl FSN. The binding tendency has been found to be related to the hydrophobicity of the medium. Conclusion: Interactions between different surfactants and amphiphilic drug PC HCl showed that binding tendency of PC HCl followed the order as; Zonyl FSN > Tween 20 > SDS > CTAB > LSB and presence of Zonyl FSN micelles increased incorporation of PC HCl to all types of micelles.
Keywords: Procaine hydrochloride; zonyl FSN-100; surface active drugs; surfactants; micelle; interaction; binding constant; DRUG AMITRIPTYLINE HYDROCHLORIDE; CATIONIC SURFACTANT; BETA-CYCLODEXTRIN; AMPHIPHILIC DRUG; CETYLTRIMETHYLAMMONIUM BROMIDE; PROMETHAZINE HYDROCHLORIDE; MICELLAR SOLUBILIZATION; MIXED MICELLIZATION; ANIONIC SURFACTANT; SOLUTION BEHAVIOR